What Drives Regional Disparities in Educational Expansion: School Reform, Modernization, or Social Structure? - Marcel Helbig; Norbert Sendzik (Education Sciences, 2022)
The aim of this study is to empirically investigate the reasons for regional disparities in educational expansion in Germany (i.e., rising rates of general university entrance qualification) on the basis of theoretically relevant influencing factors: changes in school policies, changes in social structure, or general social modernization processes. We pay special attention to the legal framework of schools, which has changed at different times in the German states. Our analysis is based on data from the National Educational Panel Study and on a database on the development of schooling regulations in the German states after World War II. For the analysis, we use two-way crossed random-effects models. Our analyses show that the modernization of school structures is only associated with increasing individual opportunities to access higher school education. However, this association disappears when controlling for social structure and cohort sequence. Rather, the educational expansion of the recent decades is characterized by a changed social structure and, in small parts, by general social modernization processes. In light of our findings, we argue that educational policy adapts school structures to societal changes, opens up new opportunities, yet at the same time reproduces and exacerbates educational inequality.
Additional information: Open access publication of this article was funded by the Open Access Fund of the Leibniz Association and WZB Berlin Social Science Center.
Keywords: 330; educational expansion; educational inequality; educational policy; regional disparities; Germany